In Vitro Cultivation of the Syphilis Spirochete Treponema pallidum. Issue 2 (17th February 2021) - Edmondson, Diane G.; Norris, Steven J.
Abstract: For over a century, investigation of Treponema pallidum subsp. pallidum, the spiral‐shaped bacterium that causes syphilis, was hindered by an inability to culture the organism in vitro. A recent breakthrough has enabled continuous in vitro growth of this organism in co‐culture with mammalian tissue culture cells. This article contains the protocols needed to culture T. pallidum in the standard laboratory environment. In addition, protocols for growing and maintaining the required tissue culture cells, for generating isogenic strains by limiting dilution, and for quantitating T. pallidum by darkfield microscopy are included. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : In vitro cultivation of T reponema pallidum Basic Protocol 2 : Generation of isogenic strains Support Protocol 1 : Alternate harvest procedure Support Protocol 2 : Culture of Sf1Ep cells Support Protocol 3 : Assessment of T. pallidum number and viability